2009
DOI: 10.1161/circulationaha.108.843763
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparity Persists After On-Pump and Off-Pump Coronary Artery Bypass Grafting

Abstract: Background-Race has been shown to be an independent risk factor for operative mortality after coronary artery bypass grafting (CABG). This study sought to determine the extent to which race is a risk factor for adverse events, long-term mortality, and whether off-pump surgery (OPCAB) modifies that risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…[1][2][3][4][5] However, results of CABG surgery have improved markedly over the past decade and it is unclear whether these older data reflect contemporary outcomes. Additionally, some of these previous studies evaluated data from a single state or small group of institutions and may not reflect national results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] However, results of CABG surgery have improved markedly over the past decade and it is unclear whether these older data reflect contemporary outcomes. Additionally, some of these previous studies evaluated data from a single state or small group of institutions and may not reflect national results.…”
mentioning
confidence: 99%
“…Previously hypothesized explanations for the disparities in outcomes have included demographics and socioeconomic differences, comorbid illness, disease severity, and presenting characteristics. [1][2][3][4][5] The association of the hospital and physician characteristics, and the quality of care delivered to these patients, as well, with the race-related differences in outcomes after CABG has not been fully elucidated.…”
mentioning
confidence: 99%
“…It has been shown that patients with preexisting low ejection fraction (EF) are at a higher risk of developing respiratory problems than patients with normal EF (11,12,(32)(33)(34)(35)(36). Impaired left ventricular ejection fraction (LVEF) of less than 30%, history of previous myocardial infarction (36,37), and preexisting congestive heart failure, age, diabetes mellitus and arterial hypertension, have all been shown to be independent, significant predictors for developing these respiratory problems (30,31,35).…”
Section: Underlying Function Of the Left Ventriclementioning
confidence: 99%
“…It has also been demonstrated that in patients undergoing CABG combined with valve disease, there is an increased possibility that the patients would require readmission to the ICU. In such patients, post-operative respiratory complications are the most common reasons for readmission (32)(33)(34)(36)(37)(38). In addition, a history of myocardial infarction during the last 90 days and a previous history of cardiac surgery, are both considered to be important predictors of postoperative respiratory problems (36-40).…”
Section: Underlying Function Of the Left Ventriclementioning
confidence: 99%
See 1 more Smart Citation